PERIWAYATAN HADIS: ANALISIS TEKNIK, SYARAT, DAN METODE - Fahman, Azzah Fadiyah Nurfadhilah; Muhammad Ali Ngampo; Tasmin Tangngareng (As-Sulthan Journal of Education, 2025)
This study aims to analyze the techniques and methods used in the transmission of Hadith, as well as the conditions that must be fulfilled in the process of transmission. The research employs a library research method, examining various literature and reliable sources related to the transmission of Hadith. The primary focus of this study is to understand the different techniques of Hadith transmission, whether it involves transmission through exact wording (oral transmission) or through meaning (translation or interpretation), as well as to identify the conditions required for a Hadith to be accepted as a valid narration. In the transmission of Hadith, several methods are used, including As-Sima' (direct hearing), Al-Qiroah (reading), Al-Ijazah (permission to transmit), Al-Munawalah (providing written works or books), Al-Mukatabah (written communication), Al-I'lam (notification without permission), Al-Washiyah (written will), and Al-Wijdan (finding narrations in books). The results of this study show that each transmission method has its own characteristics and role in maintaining the authenticity and authority of Hadith. Additionally, conditions such as the integrity of the narrators, the consistency of the chain of narrators (sanad), and the alignment of the Hadith text (matan) with historical facts are crucial in ensuring the validity of accepted narrations. In conclusion, a deep understanding of the techniques, methods, and conditions for Hadith transmission is essential to preserving the authenticity of Islamic teachings and passing down the legitimate knowledge to future generations.